Novel sodium ion battery halide solid electrolyte
By using a novel sodium-ion electrolyte preparation process that combines sodium chloride and sodium fluoride with nano-silica and zinc bromide sintering aid, the stability and conductivity problems of existing halide solid electrolytes have been solved, realizing a halide solid electrolyte with high ionic conductivity and a wide electrochemical window, suitable for sodium-ion batteries.
Patent Information
- Application Number
- CN202511610019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-01-30
AI Technical Summary
Existing halide solid electrolytes suffer from insufficient air stability, susceptibility to moisture, limited synthesis methods, and a tendency to react with electrodes during long-term cycling, resulting in high grain boundary impedance and poor cycling stability, which limits their commercial application.
A novel sodium-ion battery halide solid electrolyte with high ionic conductivity and a wide electrochemical window was prepared by using tantalum chloride and sodium fluoride as raw materials, doping with nano-silica and zinc bromide sintering aids, and combining a two-step heat treatment process.
The process achieved electrolyte densification and ion conduction pathway optimization, improving the structural stability and ionic conductivity of the material, reducing grain boundary impedance, and broadening the electrochemical window, making it suitable for large-scale production.
Smart Images

Figure CN121439893A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of electrolyte materials, and particularly relates to a novel halide solid-state electrolyte for sodium ion batteries. BACKGROUND
[0002] The resource bottleneck and safety hazards of lithium batteries promote the research of sodium ion batteries. The lithium crust reserves are only 0.0065%, and are concentrated in a few areas, resulting in high raw material cost. Meanwhile, the liquid electrolyte is prone to leakage, thermal runaway and dendrite growth, which limits its large-scale application. Under this background, sodium ion batteries become an ideal alternative solution.
[0003] The core superiority of sodium ion batteries is reflected in three aspects: first, sodium resources are abundant (2.36% in the earth's crust, and a large amount exists in seawater), and the price of sodium salt is only 1 / 10 of that of lithium salt; second, the safety is higher, the thermal stability is excellent, and there is no risk of dendrite growth; third, the cost advantage is significant, the current collector can use cheap aluminum foil, the overall cost is reduced by more than 30% compared with lithium batteries, and the low-temperature performance and fast charging capacity are outstanding.
[0004] Halide solid-state electrolyte is a solid-state ion conductor composed of halide anions (Cl - , Br - , I - , etc.) and metal cations, which can be divided into divalent, trivalent and tetravalent according to the valence of metal ions, and provides a safe and efficient ion transmission channel for sodium ion batteries. Compared with other electrolytes, it has unique advantages. Compared with oxide electrolyte, the interface compatibility is better, and there is no problem of brittleness and difficult processing; compared with sulfide electrolyte, the chemical stability is stronger, and it is not easy to hydrolyze to produce toxic gas; compared with polymer electrolyte, the room temperature ionic conductivity is higher, and it does not need high temperature working environment.
[0005] At present, halide solid-state electrolyte still has key bottlenecks, such as insufficient air stability, easy to be affected by water vapor, limited synthesis method, resulting in high grain boundary impedance, easy to react with electrodes in long-term cycle, and cycle stability needs to be improved. These problems become the main obstacles for its commercial application, and it is urgent to break through through material modification and process innovation.
[0006] The Chinese invention patent application with the publication number CN116683018A discloses a preparation method of halide solid-state electrolyte, halide solid-state electrolyte and its application. The raw materials include first metal halide and second metal halide, the metal elements in the first metal halide contain Ta, the metal elements in the second metal halide contain Na, and the halogen elements contain Cl and F. The solvent is added in the ball milling process, which can improve the structural stability of the prepared halide solid-state electrolyte. After annealing treatment, the crystal structure of the halide solid-state electrolyte changes little, and the crystallinity is low and the ionic conductivity is high.
[0007] However, the halide electrolyte prepared by traditional high-energy ball milling will cause the decomposition, volatilization or unfavorable crystal transformation of the main electrolyte phase at high temperature, resulting in the decrease of the density of the electrolyte sheet, affecting the interface contact and conductivity in the actual battery. SUMMARY
[0008] The purpose of the present application is to provide a new type of sodium ion battery halide solid electrolyte, which is prepared by using tantalum chloride and sodium fluoride as raw materials, doping a sintering aid composed of nano-silicon dioxide and zinc bromide to synergistically promote material densification and ion conduction path optimization, and innovatively adopting a two-step heat treatment process, thereby preparing a new type of sodium ion battery halide solid electrolyte with high ion conductivity and wide electrochemical window.
[0009] The purpose of the present application can be achieved by the following technical solutions: A new type of sodium ion battery halide solid electrolyte, comprising a halide electrolyte matrix 100 parts and a sintering aid 3-8 parts by mass fraction; The molecular formula of the halide electrolyte matrix is: Na X TaCl5F X , X=1-3.
[0010] Further, the halide electrolyte matrix is prepared by the following steps: The electrolyte matrix mixed powder is cold isostatic pressed in an argon glove box to press a green sheet body with a diameter of 10 mm and a thickness of 1 mm, the green sheet body is transferred to a tube furnace, heated to 300℃ at a rate of 5℃ / min under argon atmosphere, and then cooled with the furnace, crushed to obtain the halide electrolyte matrix.
[0011] Further, the pressure of cold isostatic pressing of the green sheet body is 200-250MPa, and the pressure holding time is 5min.
[0012] Further, the electrolyte matrix mixed powder is prepared by the following steps: The tantalum chloride and sodium fluoride are ball milled at a speed of 400-600rpm for 12-18h using a planetary ball mill, and sieved to obtain the electrolyte matrix mixed powder.
[0013] Further, the molar ratio of tantalum chloride to sodium fluoride is 1:1-3.
[0014] Further, the sintering aid is prepared by the following steps: The nano-silicon dioxide and zinc bromide are ball milled at a speed of 400-600rpm for 6h using a planetary ball mill, and sieved to obtain the sintering aid.
[0015] Further, the molar ratio of nano-silicon dioxide to zinc bromide is 1:2-4.
[0016] Further, the specific preparation process of the new type of sodium ion battery halide solid electrolyte is as follows: The halide electrolyte matrix is transferred to a planetary ball mill, ball milled at 400~600rpm for 2~3h, sintering aids are added and ball milled for 3h, then the powder is cold isostatic pressed, pressed into a precursor blank with a diameter of 10mm and a thickness of 1mm, the precursor blank is transferred to a muffle furnace, heated to 500℃ at a rate of 5℃ / min, kept for 12h, cooled, crushed, and ball milled at 400~600rpm for 6~8h to obtain the new type of sodium ion battery halide solid electrolyte.
[0017] Further, the pressure of cold isostatic pressing of the precursor blank is 250~300MPa, and the pressure holding time is 5min.
[0018] The beneficial effects of the present application are: 1. The present application combines tantalum chloride and sodium fluoride by high-energy ball milling, creating an electrolyte structure dominated by long-range disordered amorphous phase, enriching the sodium ion migration channel, and innovatively introducing nano-silicon dioxide and zinc bromide sintering aids, and adopting a two-step heat treatment process of "low-temperature pretreatment + high-temperature sintering", which synergistically realizes the densification and structural stability of the material, and finally obtains a solid electrolyte with high ionic conductivity and wide electrochemical window.
[0019] The whole process is based on mechanical alloying and solid phase reaction, with the comprehensive advantages of simple process, good repeatability and easy scale-up production, providing an effective electrolyte solution for the development of high-performance sodium ion solid-state batteries.
[0020] 2. The electrolyte matrix mixed powder in the present application realizes the high uniformity of tantalum chloride and sodium fluoride at the microscale through high-energy ball milling process, and at the same time, mechanical energy induces a large number of defects in the lattice, significantly improving the chemical reaction activity of the raw materials; this process not only initially constructs the long-range disordered amorphous phase structure, providing abundant transition sites for sodium ions, but also creates ideal high-activity precursors for the subsequent heat treatment process, becoming the structural basis and key guarantee for obtaining high-performance solid electrolyte.
[0021] 3. The sintering aid in the present application is composed of nano-silicon dioxide and zinc bromide, nano-silicon dioxide fills the crystal boundary gap as a structural framework, maintains the stability of amorphous phase, and zinc bromide forms a molten liquid phase during high-temperature sintering, greatly promoting particle rearrangement and interface fusion through liquid phase sintering mechanism, effectively reducing the crystal boundary impedance; at the same time, the introduced bromine ion acts as a lattice distortion agent, further intensifying the structural disorder and widening the sodium ion migration channel. Through the synergistic effect of physical filling and chemical regulation, the electrolyte is highly densified and the optimal ion transport network is constructed.
[0022] 4. The two-step heat treatment process in this invention achieves synergistic effects. The first step allows the ball-milled, highly active precursor to undergo stress release, structural relaxation, and preliminary solid-phase reaction, forming a structurally stable amorphous precursor. The second step, with the synergistic effect of sintering aids, promotes complete densification of the material and optimizes the continuity of the amorphous phase, ultimately obtaining an electrolyte with high ionic conductivity. This process design effectively avoids over-crystallization caused by direct high-temperature sintering, achieving a balance between high ionic conductivity and structural stability through staged control of microstructure evolution. Attached Figure Description
[0023] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the novel sodium-ion battery halide solid electrolyte prepared in Example 1. Figure 2 This is a scanning electron microscope (SEM) image of the novel sodium-ion battery halide solid electrolyte prepared in Example 1. Figure 3 The impedance spectrum of the novel sodium-ion battery halide solid electrolyte prepared in Example 1; Figure 4 Impedance spectra of the halide solid electrolytes for novel sodium-ion batteries in Examples 1-3; Figure 5 This is a summary graph of the ionic conductivity of the halide solid electrolytes for novel sodium-ion batteries in Examples 1 to 3. Figure 6 Linear sweep voltammetry curve of the novel sodium-ion battery halide solid electrolyte prepared in Example 1. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments in the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1: A novel sodium-ion battery halide solid electrolyte was prepared by the following method: S1: Tantalum chloride and sodium fluoride were transferred to the grinding jar of a planetary ball mill in a 1:1 molar ratio. Zirconia grinding balls were added, and the mixture was ball-milled at 400 rpm for 12 hours. The mixture was then sieved, and the powder product was taken out to obtain an electrolyte matrix mixed powder.
[0026] The solid phase reaction is induced by mechanical force. During the ball milling process, the particles of tantalum chloride and sodium fluoride are repeatedly broken and cold-welded to form a highly uniform composite at the microscale. Meanwhile, the mechanical energy causes a large number of defects in the crystal lattice, which activates the chemical reactivity of the raw materials.
[0027] S2: Transfer the nanosilica and zinc bromide at a molar ratio of 1:2 to the ball milling tank of the planetary ball mill, add zirconia grinding balls, and use the planetary ball mill to mill at a speed of 400 rpm for 6 h. Screen and take out the powder product to obtain the sintering aid.
[0028] S3: The electrolyte matrix mixed powder is cold isostatic pressed at 200 MPa for 5 min in an argon glove box to form a green compact sheet with a diameter of 10 mm and a thickness of 1 mm. The green compact sheet is transferred to a tube furnace, heated to 300℃ at a rate of 5℃ / min in an argon atmosphere, and held for 6 h. Then, the furnace is cooled down, and the product is crushed to obtain the halide electrolyte matrix.
[0029] S4: The halide electrolyte matrix is transferred to a planetary ball mill. After 2 h of ball milling at 600 rpm, 3 wt% of the sintering aid is added to the halide electrolyte matrix, and the ball milling is continued for another 3 h. Then, the product is cold isostatic pressed at 250 MPa for 5 min to form a precursor compact sheet with a diameter of 10 mm and a thickness of 1 mm. The precursor compact sheet is transferred to a muffle furnace and heated to 500℃ at a rate of 5℃ / min. The temperature is held for 12 h, and the furnace is cooled down to room temperature. After crushing, the product is ball milled at 600 rpm for 6 h using a planetary ball mill to obtain the new halide solid-state electrolyte for sodium-ion batteries.
[0030] In the ball milling process of steps S1, S2, and S4, the mass ratio of the zirconia grinding balls to the corresponding raw materials is 40:1, and the diameter of the zirconia grinding balls is 5 mm.
[0031] Figure 1 The X-ray diffraction pattern (XRD) of the new halide solid-state electrolyte for sodium-ion batteries prepared in this example is shown in the figure. It is found that the halide solid-state electrolyte formed by high-energy ball milling of sodium fluoride and tantalum chloride is amorphous. The introduction of fluorine greatly promotes the formation of amorphous phase with long-range disorder. These disordered regions provide a large number of transition sites with uniform energy distribution for sodium ions.
[0032] Figure 2 The scanning electron microscope image (SEM) of the new halide solid-state electrolyte for sodium-ion batteries prepared in this example is shown in the figure. It is found that the halide solid-state electrolyte shows irregularly shaped particles, indicating that it is an amorphous powder electrolyte.
[0033] Example 2: A new type of sodium-ion battery halide solid-state electrolyte is provided, which is different from Example 1 in that the molar ratio of tantalum chloride to sodium fluoride in step S1 is 1:2, and the molar ratio of nano-silicon dioxide to zinc bromide in step S2 is 1:3, to prepare a new type of sodium-ion battery halide solid-state electrolyte.
[0034] Example 3: A new type of sodium-ion battery halide solid-state electrolyte is prepared by the following preparation method: S1: Transfer tantalum chloride and sodium fluoride to the ball milling tank of the planetary ball mill at a molar ratio of 1:3, add zirconium oxide grinding balls, use the planetary ball mill to mill at a speed of 600 rpm for 18 h, sieve, and take out the powder product to obtain an electrolyte matrix mixed powder.
[0035] S2: Transfer nano-silicon dioxide and zinc bromide to the ball milling tank of the planetary ball mill at a molar ratio of 1:4, add zirconium oxide grinding balls, use the planetary ball mill to mill at a speed of 600 rpm for 6 h, sieve, and take out the powder product to obtain a sintering aid.
[0036] S3: The electrolyte matrix mixed powder is cold isostatic pressed in an argon glove box at 250 MPa for 5 min to press a green compact sheet with a diameter of 10 mm and a thickness of 1 mm, the green compact sheet is transferred to a tube furnace, heated to 300°C at a rate of 5°C / min under an argon atmosphere, and held for 6 h, then cooled with the furnace, and crushed to obtain a halide electrolyte matrix.
[0037] S4: Transfer the halide electrolyte matrix to the planetary ball mill, add 8 wt% of the sintering aid based on the halide electrolyte matrix after 3 h of 400 rpm ball milling, continue to ball mill for 3 h, then cold isostatic press at 300 MPa for 5 min to press a precursor compact sheet with a diameter of 10 mm and a thickness of 1 mm, transfer the precursor compact sheet to a muffle furnace, heat to 500°C at a rate of 5°C / min, hold for 12 h, cool to room temperature with the furnace, crush, and use the planetary ball mill to mill at 400 rpm for 8 h to obtain a new type of sodium-ion battery halide solid-state electrolyte.
[0038] Example 4: A new type of sodium-ion battery halide solid-state electrolyte is provided, which is different from Example 1 in that the sintering aid is increased to 5 wt% in step S4 to prepare a new type of sodium-ion battery halide solid-state electrolyte.
[0039] Example 5: A new type of sodium-ion battery halide solid-state electrolyte is provided, which is different from Example 1 in that the sintering aid is increased to 8 wt% in step S4 to prepare a new type of sodium-ion battery halide solid-state electrolyte.
[0040] All raw materials in the embodiments 1-5 of the present application are commercially available products.
[0041] Comparative Example 1: The difference from Example 1 is that no nano-silicon dioxide is added in step S2, and the remaining steps are unchanged, to prepare a new halide solid-state electrolyte for sodium-ion batteries.
[0042] Comparative Example 2: The difference from Example 1 is that no zinc bromide is added in step S2, and the remaining steps are unchanged, to prepare a new halide solid-state electrolyte for sodium-ion batteries.
[0043] Comparative Example 3: The difference from Example 1 is that step S3 is not performed and the halide electrolyte matrix in step S4 is replaced by the electrolyte matrix mixed powder in step S1, and the remaining steps are unchanged, to prepare a new halide solid-state electrolyte for sodium-ion batteries.
[0044] The new halide solid-state electrolyte for sodium-ion batteries prepared in Examples 1-5 and Comparative Examples 1-3 is subjected to the following performance tests: Ion conductivity test: 200 mg of the new halide solid-state electrolyte for sodium-ion batteries is weighed and placed in a solid-state battery pressure test mold, aluminum-coated carbon is spread on both sides of the solid-state electrolyte, and is pressed with a pressure of 200 MPa, and an alternating current impedance test is performed. The alternating current impedance is performed on a Biologic electrochemical workstation, and the ion conductivity is calculated according to the obtained alternating current impedance spectrum and the formula: σ = L / R; wherein σ is the ion conductivity (S / cm), L is the thickness of the electrolyte film (cm), R is the measured impedance (Ω), and S is the area of the electrolyte film (cm 2 ).
[0045] Figure 3 Impedance spectrum of the new halide solid-state electrolyte for sodium-ion batteries prepared in Example 1.
[0046] From Figure 3 It can be seen that the total impedance of the halide solid-state electrolyte is 200 Ω, and the ion conductivity of the halide solid-state electrolyte is calculated to be 0.445 mS / cm.
[0047] Electrochemical window test: 100 mg of the new halide solid-state electrolyte for sodium-ion batteries is weighed, and a 10 mm tablet press is used to press into a tablet under a pressure of 200 MPa. One side of the mold is opened, and Na3PS4 electrolyte and Na 15 Sn4 sodium-tin alloy are added in turn, followed by pressing under a pressure of 300 MPa. After pressing is completed, a mixture of the solid-state electrolyte and conductive carbon black (mass ratio 9:1) is added to the other side of the mold, and finally pressed under a pressure of 350 MPa. The assembly is completed. The electrochemical window of the solid-state electrolyte is tested by linear sweep voltammetry.
[0048] Figure 6 Linear sweep voltammetry plot of the new sodium-ion battery halide solid-state electrolyte prepared in Example 1.
[0049] From Figure 6 It can be seen that the electrochemical window of the halide solid-state electrolyte is 4.24 V.
[0050] The ion conductivity test results are shown in Table 1: Table 1 Performance test results of the new sodium-ion battery halide solid-state electrolyte From Table 1 and Figure 5 It can be seen that when the optimal molar ratio of sodium fluoride to tantalum chloride of 1:1 is used as the raw material, and the addition amount of the sintering aid composed of nano-silicon dioxide and zinc bromide with a molar ratio of 1:2 is 3wt%, and the two-step heat treatment process is used, the ion conductivity can be as high as 0.445 mS / cm, and any deviation from these parameters will cause the ion conductivity of the electrolyte to decrease.
[0051] From Comparative Example 1, it can be analyzed that the addition of nano-silicon dioxide in step S2 causes the ion conductivity of the prepared solid-state electrolyte to decrease significantly; it may be because the nano-silicon dioxide optimizes the microstructure by filling pores and promoting densification during sintering, reduces the crystal boundary resistance, and also helps to stabilize the key amorphous phase formed by the introduction of fluorine, maintaining a large number of energy-uniform sodium ion transition sites. The lack of nano-silicon dioxide will destroy this synergistic effect, leading to an increase in electrolyte structure defects and a decrease in densification, thereby hindering the conduction of sodium ions.
[0052] From Comparative Example 2, it can be analyzed that when no zinc bromide is added and only silicon dioxide is used as a sintering aid, the ion conductivity of the prepared solid-state electrolyte is higher than that of Comparative Example 1, but still significantly lower than that of Example 1; it may be because during the heat treatment process, zinc bromide can form a low-melting-point liquid phase, acting as a "binder" and mass transfer medium during the sintering process, greatly promoting the fusion and densification between the particles of the electrolyte matrix, thereby effectively reducing the crystal boundary impedance. At the same time, the bromine ions in zinc bromide can optimize the structure and composition of the amorphous phase by partial solid solution or interface modification, providing a more optimal conduction path for sodium ions.
[0053] It can be analyzed from Comparative Example 3 that, the low-temperature heat treatment of the halide electrolyte matrix in step S3 is omitted, and the electrolyte matrix mixed powder after ball milling is directly used for final sintering, which results in a sharp decrease of the ion conductivity to the lowest in all data. The process is not a simple pretreatment, but through low-temperature heat treatment, the amorphous powder in high-energy metastable state after ball milling is fully reacted in solid phase, the excessive internal stress introduced by ball milling is eliminated, the initial amorphous phase structure is stabilized, and a stable ion conduction skeleton is preliminarily constructed, which lays a chemical and structural foundation for subsequent uniform mixing with sintering aids and final high-temperature densification sintering.
[0054] Although the embodiments of the present application have been shown and described, it is to be understood that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the present application.
Claims
1. A novel sodium-ion battery halide solid-state electrolyte, characterized in that, The halide electrolyte matrix comprises 100 parts by mass of a halide electrolyte matrix and 3-8 parts by mass of a sintering aid; The molecular formula of the halide electrolyte matrix is: Na X TaCl5F X , X = 1 ~ 3.
2. A novel sodium-ion battery halide solid-state electrolyte according to claim 1, characterized by, The halide electrolyte matrix is prepared by the following steps: The electrolyte matrix mixed powder is cold isostatic pressed in an argon glove box to form a green sheet with a diameter of 10 mm and a thickness of 1 mm, the green sheet is transferred to a tube furnace, and the temperature is raised to 300 DEG C at a rate of 5 DEG C / min under an argon atmosphere, and then the temperature is kept for 6 h, and then the furnace is cooled, and the powder is crushed to obtain the halide electrolyte matrix.
3. A novel sodium-ion battery halide solid-state electrolyte according to claim 2, characterized by, The pressure of the cold isostatic pressing of the green sheet is 200-250 MPa, and the pressure holding time is 5 min.
4. A novel sodium-ion battery halide solid-state electrolyte according to claim 2, characterized by, The electrolyte matrix mixed powder is prepared by the following steps: The planetary ball mill is used to ball mill the tantalum chloride and sodium fluoride at a speed of 400-600 rpm for 12-18 h, and the powder is sieved to obtain the electrolyte matrix mixed powder.
5. A novel sodium-ion battery halide solid-state electrolyte according to claim 4, characterized by, The molar ratio of the tantalum chloride to the sodium fluoride is 1:1-3.
6. A novel sodium-ion battery halide solid-state electrolyte according to claim 1, characterized by, The sintering aid is prepared by the following steps: The planetary ball mill is used to ball mill the nanosilica and zinc bromide at a speed of 400-600 rpm for 6 h, and the powder is sieved to obtain the sintering aid.
7. A novel sodium-ion battery halide solid-state electrolyte according to claim 6, characterized by, The molar ratio of the nanosilica to the zinc bromide is 1:2-4.
8. A novel sodium-ion battery halide solid-state electrolyte according to claim 1, characterized by, The specific preparation process of the new type of sodium ion battery halide solid electrolyte is as follows: The halide electrolyte matrix is transferred to a planetary ball mill, and ball milled at 400-600 rpm for 2-3 h, the sintering aid is added and ball milled for 3 h, then the powder is cold isostatic pressed to form a precursor blank with a diameter of 10 mm and a thickness of 1 mm, the precursor blank is transferred to a muffle furnace, and the temperature is raised to 500 DEG C at a rate of 5 DEG C / min, and then the temperature is kept for 12 h, and then the furnace is cooled, and the powder is crushed, and then ball milled at 400-600 rpm for 6-8 h to obtain the new type of sodium ion battery halide solid electrolyte.
9. A novel sodium-ion battery halide solid-state electrolyte according to claim 8, characterized by, The pressure of the cold isostatic pressing of the precursor blank is 250-300 MPa, and the pressure holding time is 5 min.
Citation Information
Patent Citations
Preparation method of halide solid electrolyte, halide solid electrolyte and application of halide solid electrolyte
CN116683018A
Cited By
Air-stable sodium-ion battery halide solid-state electrolyte and applications thereof
CN122494783A